2006
DOI: 10.1063/1.2140282
|View full text |Cite
|
Sign up to set email alerts
|

Diffusivity, excess entropy, and the potential-energy landscape of monatomic liquids

Abstract: The connection between thermodynamic, transport, and potential-energy landscape features is studied for liquids with Lennard-Jones-type pair interactions using both microcanonical molecular-dynamics and isothermal-isobaric ensemble Monte Carlo simulations. Instantaneous normal-mode and saddle-point analyses of two variants of the monatomic Lennard-Jones liquid have been performed. The diffusivity is shown to depend linearly on several key properties of instantaneous and saddle configurations-the energy, the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…24 This feature is encoded, in an effective way, in a number of models of energy landscapes developed in the last years, 25,26,27,28 and has sometimes been addressed in numerical simulations. 29 Statistical properties of high-order stationary points of the PES have been investigated recently for a variety of monoatomic and binary systems, both in the liquid 30,31 and supercooled regime. 17,32 The existence of some universal features in the energy landscape of different model liquids 17,32 has been highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…24 This feature is encoded, in an effective way, in a number of models of energy landscapes developed in the last years, 25,26,27,28 and has sometimes been addressed in numerical simulations. 29 Statistical properties of high-order stationary points of the PES have been investigated recently for a variety of monoatomic and binary systems, both in the liquid 30,31 and supercooled regime. 17,32 The existence of some universal features in the energy landscape of different model liquids 17,32 has been highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…For simple spherical particle fluids, the two-body excess entropy is found to account for more than 90% of the total excess entropy (31,32). The two-body excess entropy scaling has found widespread use in predicting the dynamics of, for example, metallic and hydrogen-bonding liquids such as water (23,(33)(34)(35)(36)(37). From a practical point of view, it is easier to calculate the twobody excess entropy requiring only knowledge of g(r) rather than calculating the full excess entropy that may require sophisticated free-energy methods (24).…”
mentioning
confidence: 99%
“…20 Here we extend the earlier study by considering the correlation of a wider range of landscape properties which could potentially be correlated with the available configurational volume as well as by examining the liquid at several state points in the neighborhood of the freezing transition, both in the stable and supercooled regimes. 1 Our recent work on pair-additive Lennard-Jones liquids in the stable liquid regime where the Dzugutov scaling relationship holds showed that diffusivity, and therefore also the exponential of the excess entropy, depends linearly on several landscape properties, such as mean curvature and the fraction of negative curvature directions associated with the instantaneous configurations sampled from a suitable ensemble probability distribution.…”
Section: Introductionmentioning
confidence: 72%
“…10,20 No spherical potential cutoff was required for the densities and simulation cell sizes used here. Parameter a fixes the length of the interaction, so that the attraction is smoothly truncated to zero at r = a. Parameters A and a are chosen to reproduce the location and depth of the minimum in the 12-6 Lennard-Jones potential and are set to A = 6.767 441 and a = 2.464 918 32.…”
Section: Computational Detailsmentioning
confidence: 99%